ANALYSIS OF GENERATION Z’S BEHAVIOR IN USING SHARIA FINTECH IN THE DIGITAL ERA - Surotul Lubna; Kuni Badriatul (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2026)
The rapid development of digital technology has transformed the financial services industry and encouraged the emergence of Islamic Financial Technology (Islamic Fintech) as an innovative solution for providing Sharia-compliant financial services. As digital natives, Generation Z has become one of the most influential consumer groups in adopting digital financial services due to their high level of technological literacy and frequent engagement with digital platforms. However, despite the growing popularity of fintech, the adoption of Islamic fintech among Generation Z remains relatively limited compared to conventional fintech services. Therefore, this study aims to analyze the behavior of Generation Z in using Islamic fintech in the digital era by examining the influence of perceived usefulness, perceived ease of use, Islamic financial literacy, religiosity, and social influence. This study employs a quantitative research approach using a survey method. Data were collected through questionnaires distributed to Generation Z respondents who are familiar with or have experience using Islamic fintech services. The collected data were analyzed using descriptive and inferential statistical techniques to identify the factors influencing the adoption of Islamic fintech. The findings indicate that perceived usefulness and perceived ease of use significantly influence Generation Z’s intention to adopt Islamic fintech services. In addition, Islamic financial literacy plays an important role in increasing awareness and understanding of Sharia-compliant financial products. Religiosity also positively affects users’ preferences for Islamic fintech, while social influence from family, peers, and social media contributes to shaping adoption behavior. These findings suggest that the adoption of Islamic fintech among Generation Z is influenced by a combination of technological, educational, religious, and social factors. The study concludes that enhancing Islamic financial literacy, improving service quality, and strengthening public awareness of Sharia-compliant digital financial services are essential strategies for increasing Islamic fintech adoption among Generation Z. The findings are expected to contribute to the development of Islamic fintech and support the growth of the Islamic digital economy in Indonesia.